2017
DOI: 10.1111/jphp.12712
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of anti-inflammatory effect and possible mechanism of action of Tibouchina granulosa

Abstract: Taken together, our results indicate that leaves of T. granulosa present anti-inflammatory effect and can be useful in the preparation of new phytomedicines.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 28 publications
0
10
0
Order By: Relevance
“…Bioactive ingredients present in nutraceuticals have exhibited diverse pharmacological properties such as antioxidant, sedative, hypnotic, anti-inflammatory, immuno-modulatory and adaptogenic attributes [ 219 , 220 , 221 , 222 , 223 ]. Subsequently, these products were applied and their efficiency appraised using in vitro, in vivo, in silico, high-throughput in vitro, and omics technology-reliant assays [ 224 ]. Furthermore, various animal models have been used for in vivo, invasive, and non-invasive studies depending upon study design [ 225 ].…”
Section: Nutraceuticals’ Safety On Consumersmentioning
confidence: 99%
“…Bioactive ingredients present in nutraceuticals have exhibited diverse pharmacological properties such as antioxidant, sedative, hypnotic, anti-inflammatory, immuno-modulatory and adaptogenic attributes [ 219 , 220 , 221 , 222 , 223 ]. Subsequently, these products were applied and their efficiency appraised using in vitro, in vivo, in silico, high-throughput in vitro, and omics technology-reliant assays [ 224 ]. Furthermore, various animal models have been used for in vivo, invasive, and non-invasive studies depending upon study design [ 225 ].…”
Section: Nutraceuticals’ Safety On Consumersmentioning
confidence: 99%
“…Mice were tested using the method described by Sobrinho et al, [21]. Animals were placed on a hot plate (Insight Equipment, São Paulo, Brazil) set at 55 ± 1 °C.…”
Section: Methodsmentioning
confidence: 99%
“…Studies of the biological potential of the family Melastomataceae have demonstrated that its species have analgesic, antioxidant, antimicrobial, anti-inflammatory activities (Vasconcelos et al, 2006;Andreo et al, 2006;Sobrinho et al, 2017;Bomfim et al, 2020). These activities may be associated with the presence of several secondary metabolites such as flavonoids, tannins, terpenes and anthocyanidins (Calderón et al, 2002;Serna and Martínez, 2015;Bomfim et al, 2020) which are synthesized by plants in response to environmental conditions and often during specific stages of their development.…”
Section: Introductionmentioning
confidence: 99%